(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to determine and analyze the effect of sanctions on the discipline of the State Civil Aparatus of the Bombana Regency Transportation Servise. This study user quantitative type whit the survey method. The number of population were all employees at the office of Transportation Bombana Regency as many as 40 people. Sampling using saturated sampling. The results found there was a significant effect by measuring two variables X Sanctions whit the following indicator items: light punishment, moderate punishment, and severe punishment with a result of 85.1% in the very good category and the Y Discipline Variable with the following indicator items: progressive discipline and corrective discipline whit the result of 89.7% in the very good category. Meanwhole, the sanction variable had a significant effect on discipline whit a significant level of 0.001 <from the significant level of 0.05. Keywords:Eeffect of sanctions, discipline of state civil servants